Solve QUESTION No. 8.
thanks ❤️
Attachments:
![](https://hi-static.z-dn.net/files/d9d/9a0914dcf6077d6ed5f3315d31ab2db1.jpg)
Answers
Answered by
1
kx + y = k^2
=> kx + y - k^2 = 0
a1 = k
b2 = 1
c1 = - k^2
______________
x + ky = 1
=> x + ky - 1 = 0
a2 = 1
b2 = k
c2 = - 1
Now,
For infinite solutions,
a1 / a2 = b1 / b2 = c1 / c2
=> k / 1 = 1 / k = k^2 / 1
From (1) and (2), we get
k/1 = 1 /k
=> k^2 = 1
=> k = +1 and - 1 -------(A)
Now,
From (1) and (3), we get
k/1 = k^2 /1
=> k = k^2
=> 1 = k --------(B)
From equation A and B, we can say that there is only one value of k that satisfy the given condition.
Required value of k = 1
=> kx + y - k^2 = 0
a1 = k
b2 = 1
c1 = - k^2
______________
x + ky = 1
=> x + ky - 1 = 0
a2 = 1
b2 = k
c2 = - 1
Now,
For infinite solutions,
a1 / a2 = b1 / b2 = c1 / c2
=> k / 1 = 1 / k = k^2 / 1
From (1) and (2), we get
k/1 = 1 /k
=> k^2 = 1
=> k = +1 and - 1 -------(A)
Now,
From (1) and (3), we get
k/1 = k^2 /1
=> k = k^2
=> 1 = k --------(B)
From equation A and B, we can say that there is only one value of k that satisfy the given condition.
Required value of k = 1
Similar questions